Place-Based Dialogics: Adaptive Cultural and Interpersonal Approaches to Environmental Conservation - Sowards, Stacey K.; Tarin, Carlos A.; Upton, Sarah D. (Frontiers in Communication, 2017)
This study examines conservation campaigns and how they employ place-based interpersonal communication tactics to better engage local communities in rural locations in Indonesia, Philippines, and Colombia. In collaboration with the non-governmental organization Rare, the authors explore how social marketing campaigns coupled with interpersonal communication can influence communities that are often considered the most marginalized and affected by environmental problems. Field research was conducted in Indonesia since 2008 and Colombia since 2014. Ethnography through participant observation and interviews were primary methods for data collection as well as a thorough analysis of organizational documents, such as websites, blogs, reports, and other written work. Using theories of dialogue and place-based studies of interpersonal communication, three key campaign strategies emerged from our research. First, cooperative engagement through semi-formalized information sharing is an important component of building a campaign in rural areas, which might include key stakeholder meetings, relationship building with local governmental, religious, and community leaders, and training sessions with local farmers or fishers. A second approach is based on critical listening and understanding through word of mouth involvement, such as community activities and improved understanding of the challenges that local people face in their communities. Finally, a third approach relates to the recognition of difference through engaging local culture. Campaign managers have used religious leaders, local languages, traditional customs and activities, and other place-based approaches to create inclusive conservation campaigns. These strategies demonstrate that conservation campaigns require intense interpersonal dialogue, long-term commitment, and place-based understanding.